Use of a choice-based survey approach to characterise fishing behaviour in a scallop fishery. (December 2016) - Shepperson, Jennifer; Murray, Lee G.; Mackinson, Steven; Bell, Ewen; Kaiser, Michel J.
Abstract: The predictability of fisher behaviour is an area of considerable uncertainty in fisheries management models. Fisher-derived data could underpin a better understanding, and more realistic predictions of fishing behaviour. Face to face interviews and a choice-based survey were conducted with scallop fishers to collect foraging parameters that could inform a model of fishing behaviour, and to better understand patch choice behaviour. Importantly, we validated survey data against vessel monitoring system and logbook data where possible, demonstrating a good level of accuracy. Environmental parameters central to patch choice were determined (e.g. wave height, distance to port), and three strategies of patch choice behaviour were identified, termed quantity maximiser, quality maximiser, and efficient fisher. Individuals' VMS and logbook data further confirmed and explained these behavioural patterns. This approach provided reliable, highly relevant data for the parameterisation of a fisheries behavioural model, which could lead to more robust and realistic predictive fisheries models. Highlights: Data was collected directly from fishers to better understanding fishing behaviour. Face to face interviews and a conjoint analysis were completed with scallop fishers. Foraging and environmental parameters central to patch choice were identified. Different strategies of patch choice were identified, and verified against vessel data. These relevant and reliable data could lead to a more realistic behavioural model.